HUBUNGAN KOMPETENSI PROFESIONAL GURU DENGAN MINAT BELAJAR SISWA KELAS XI MATA PELAJARAN PAI DI SMK NEGERI KARANGPUCUNG - Kartika Wanojaleni (QALAM: JURNAL PENDIDIKAN ISLAM, 2024)
This research is motivated by the importance of abilities related to competence as an educator. One of the competencies possessed by teachers is professional competence. It is hoped that the professional competence possessed by teachers can arouse students' interest, especially in PAI subjects. Based on this background, researchers want to find out more about the relationship between teacher professional competence and students' interest in learning in PAI subjects.This type of research is field research using a quantitative approach with a total of 125 students as respondents using a simple random sampling technique. Data collection used four methods, namely observation, interviews, documentation and questionnaires. Observation and interview methods were carried out to determine the picture of teachers' professional competence and interest in learning in PAI subjects. Documentation method to find out tools to support teacher professional competence. while the questionnaire method was implemented to obtain data regarding teachers' professional competence and students' learning interests.The results of this research show that there is a significant relationship between teacher professional competence and interest in studying Islamic Religious Education in class